2007
DOI: 10.1111/j.1399-5448.2007.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of CTLA-4 polymorphism and human leukocyte antigen genotype for the induction of diabetes-associated cytokine response in healthy school children

Abstract: The increased IFN-gamma response and lower IL-4 response toward diabetes-related autoantigens shown in CTLA-4 +49 GG risk subjects show a possible mechanism for the association between CTLA-4 and T1D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…In combination with previous reports, the role of CTLA-4 in T1D with increasing age can be understood as partly due to the fact that different environmental factors can trigger autoimmune processes in different age groups. The role of CTLA-4 gene has been evident from a clinical perspective in several studies in association with early diagnosis, differential cytokines profile, and recently with differences between fulminant T1D and so-called classic T1D [36,37]. This information is concordant with our data about similar associations in T1D in Chilean children.…”
Section: Discussionsupporting
confidence: 94%
“…In combination with previous reports, the role of CTLA-4 in T1D with increasing age can be understood as partly due to the fact that different environmental factors can trigger autoimmune processes in different age groups. The role of CTLA-4 gene has been evident from a clinical perspective in several studies in association with early diagnosis, differential cytokines profile, and recently with differences between fulminant T1D and so-called classic T1D [36,37]. This information is concordant with our data about similar associations in T1D in Chilean children.…”
Section: Discussionsupporting
confidence: 94%
“…Peptides with overlapping sequence from HSP60, were detected in DQ8, DQ2-8, and DQ8-2 samples. These peptide sequences, as well as an additional HSP60 peptide eluted from DQ2-8 and three IA-2 peptide sequences eluted from DQ8, DQ2-8, and DQ8-2 samples have been previously reported as positive stimulators in autoreactive CD4 + T-cell activation assays (Table 1) [39][40][41][42][43][44][45][46][47][48][49][50][51][52]. We also confirmed that the ZnT8 peptide binds T1D-susceptible DQ molecules with relatively higher binding affinity than the pan-DQ binding peptide, CLIP1 (Fig.…”
Section: Direct Analysis Of Dq-bound Clip and T1d-associated Autoantimentioning
confidence: 96%
“…Interestingly, our results further indicated that +49 G/A affected CTLA-4 expression in FoxP3 hi , but not CD25 hi Foxp3 + activated Treg subsets. Several studies also indicated that PHA or peptide of heat shock protein 60 induced a higher IFN-γ response, while GAD65 induced a lower IL-4 secretion in subjects with risk GG genotype of +49 G/A 29 , 30 , one of the interpretations might be individuals with G allele had lower CTLA-4 expression in Treg subsets and reduced suppressive function. It should be noted that CTLA-4 also expressed by diverse cell types, including activated CD4+ conventional T (Tconv) cells, activated B cells, and CD8 T cells 31 – 33 .…”
Section: Discussionmentioning
confidence: 99%